Cardiopulmonary bypass and intra‐aortic balloon pump use is associated with higher short and long term mortality after transcatheter aortic valve replacement: A PARTNER trial substudy. Issue 2 (3rd February 2015) - Shreenivas, Satya S.; Lilly, Scott M.; Szeto, Wilson Y.; Desai, Nimesh; Anwaruddin, Saif; Bavaria, Joseph E.; Hudock, Kristin M.; Thourani, Vinod H.; Makkar, Raj; Pichard, Augusto; Webb, John; Dewey, Todd; et al.
Abstract : Background: Transcatheter aortic valve replacement (TAVR) with the balloon‐expandable Sapien transcatheter heart valve improves survival compared to standard therapy in patients with severe aortic stenosis (AS) and is noninferior to surgical aortic valve replacement (AVR) in patients at high operative risk. Nonetheless, a significant proportion of patients may require pre‐emptive or emergent support with cardiopulmonary bypass (CPB) and/or intra‐aortic balloon pump (IABP) during TAVR due to pre‐existing comorbid conditions or as a result of procedural complications.Objectives : We hypothesized that patients who required CPB or IABP would have increased periprocedural complications and reduced long‐term survival. In addition, we sought to determine whether preprocedural variables could predict the need for CPB and IABP.Methods : The study population included 2, 525 patients in the PARTNER Trial (Cohort A and B) and the continuing access registry (CAR). Patients that received CPB or IABP were compared to patients that did not receive either, and then further divided into those that received support pre‐TAVR and those that were placed on support emergently.Results : One‐hundred sixty‐three patients (6.5%) were placed on CPB and/or IABP. The use of CPB or IABP was associated with higher 1 year mortality (49.1% vs. 21.6%, P < 0.001). In multivariable analysis, utilization of CPB or IABP was an independent predictor of 30 day (HR 6.95) and 1‐year (HR 2.56) mortality. Although mortality was highest in emergent cases, mortality was also greater in planned CPB and IABP cases compared with non‐CPB/IABP cases (53.3% and 40.3% vs. 21.6%, P < 0.001).Conclusions : These findings indicate that CPB and IABP use in TAVR portends a poor prognosis and its utilization, particularly in the setting of pre‐emptive use, needs reconsideration. © 2015 Wiley Periodicals, Inc.